Annotated checklist of Solanum L. (Solanaceae) for Peru - Särkinen, Tiina (2015)
The genus Solanum is among the most species-rich genera both of the Peruvian flora and of the tropical Andes in general. The present revised checklist treats 276 species of Solanum L., of which 253 are native, while 23 are introduced and/or cultivated. A total of 74 Solanum species (29% of native species) are endemic to Peru. Additional 58 species occur only in small number of populations outside Peru, and these species are here labelled as near-endemics to highlight the role Peru playes in their future protection. Species diversity is observed to peak between 2500 – 3000 m elevation, but endemic species diversity is highest between 3000 – 3500 m elevation. Cajamarca has the highest number of endemic (29 spp.) and total species (130 spp.), even when considering the effect of area. Centers of endemic species diversity are observed in provinces of Cajamarca (Cajamarca), Huaraz and Carhuaz (Ancash), and Canta and Huarochirí (Lima). Secondary centres of endemism with high concentrations of both endemics and near-endemics are found in San Ignacio and Cutervo (Cajamarca), Santiago de Chuco (La Libertad), Oxapampa (Pasco), and Cusco (Cusco). Current diversity patterns are highly correlated with collection densities, and further collecting is needed across all areas, especially from Arequipa, Ayacucho, Puno, Ancash, Huánuco, Amazonas and Cajamarca, where high levels of species diversity and endemism are indicated but only a few collections of many species are known.